NURSING STUDENTS’ POST COVID-19 PANDEMIC QUALITY OF LIFE BASED ON DEMOGRAPHIC CHARACTERISTIC - Hafitriany, Syifa Aulia; Somantri, Irman; Sukmawati, Sukmawati (LPPM Institut Pendidikan Nusantara Global, 2024)
Introduction: Post Covid-19 pandemic, there was a change in nursing student habits that needed adaptability and it is important to pay attention to their quality of life. The aim of this research is to describe the Quality of Life of Post-Covid-19 Nursing Students Based on Individual Demographic Characteristics. Method: A quantitative descriptive design with a proportional stratified sampling technique to 276 of 892 nursing students was conducted in April 2023. Data were collected using the WHOQOL-BREF questionnaire to measure quality of life. This study used descriptive analysis for numerical data displayed in cross tables. Results: it was found that the quality of life of respondents tended to be good in the physical (68.25+11.27), psychological (59.78+13.62), social (68.18+15.78), and environmental (66.42+12.68) Based on the total of quality of life domains, male respondents had a higher average score than female respondents. Based on education level, it was found that respondents who were in professional programs had a higher quality of life score than those in Undergraduate Nursing Study Programs, while for history of exposure, it was found that in total, people who had been exposed had a higher quality of life than those who had not been exposed to COVID-19. Conclusions: The quality of life for nursing students after the Covid-19 pandemic has tended to be the highest level of well-being. It is necessary to identify students’ barriers in maintaining and improving their quality of life, especially in the psychological domain identified as the lowest domain.